PENGARUH PELAKSANAAN METODE DISKUSI TERHADAP MOTIVASI BELAJAR SISWA KELAS IX A DAN KELAS IX B PADA MATA PELAJARAN FIKIH DI MTS NEGERI BATANG KECAMATAN SUBAH - Kamelia, Hida; Nalim, Nalim (Dahzain Nur, 2025)
The purpose of this research is to describe the implementation of the discussion method in the subject of Fiqh at MTs Negeri Batang, to understand students' learning motivation in the subject of Fiqh, and to determine the effect of the implementation of the discussion method on students' learning motivation in the subject of Fiqh at MTs Negeri Batang. This research is a quantitative study with a field research type, using a quasi-experimental method and a nonequivalent control group design. The subjects of the study consist of two classes: IXA (experimental group) and IXB (control group). Data were collected through written tests (pretest-posttest), questionnaires, and documentation, and were analyzed using the t-test with SPSS 16. The results of the study show that the calculated t value = 6.156 with a significance value (2-tailed) of 0.000 < 0.05, thus the null hypothesis (H0) is rejected and the alternative hypothesis (Ha) is accepted. It can be concluded that there is a significant difference in the average learning outcomes of students between the discussion method and conventional learning methods, indicating that the discussion learning method has a significant effect on students' learning motivation in the subject of Fiqh at MTs Negeri Batang, Subah District.